Catalytic Promiscuity of cGAS: A Facile Enzymatic Synthesis of 2′‐3′‐Linked Cyclic Dinucleotides. (4th August 2020) - Rosenthal, Katrin; Becker, Martin; Rolf, Jascha; Siedentop, Regine; Hillen, Michael; Nett, Markus; Lütz, Stephan
Abstract: Cyclic GMP‐AMP synthase (cGAS) is a cytosolic DNA sensor that catalyzes the synthesis of the cyclic GMP‐AMP dinucleotide 2′3′‐cGAMP. 2′3′‐cGAMP functions as inducer for the production of type I interferons. Derivatives of this important second messenger are highly valuable for pharmaceutical applications. However, the production of these analogues requires complex, multistep syntheses. Herein, human cGAS is shown to react with a series of unnatural nucleotides, thus leading to novel cyclic dinucleotides. Most substrate derivatives with modifications at the nucleobase, ribose, and the α‐thio phosphate were accepted. These results demonstrate the catalytic promiscuity of human cGAS and its utility for the biocatalytic synthesis of cyclic dinucleotide derivatives. Abstract : Enzymatic shortcut : Cyclic dinucleotides, which are of great interest to study immunology and immune oncology, can be synthesized in a one‐step biotransformation significantly shortening the chemical synthesis route. The enzyme displays a surprisingly large substrate scope.